Documenting Administration System On RT 012 Pinang Ranti Using Visual Basic 6.0. - Mohammed Irfan; Aqwam Rosadi Kardian, SKom., MM (Jurnal Sistem Informasi, 2008)
Science and computer technology is more sophisticated now and spread so rapidly, so it is very helpful in the process of data processing still using manual systems. Certainly be very useful and more effective and efficient in terms of time and effort, if the data collection activities of citizens in environmental Neighborhood (RT) can be done with a computerized system. In connection with these authors are interested in making an administrative program design of computerized data collection citizen. And discuss also the Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD), Normalization and the appearance of the Visual Basic 6.0 program.